The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/admt.202101008
|View full text |Cite
|
Sign up to set email alerts
|

A Self‐Assembly Method for Tunable and Scalable Nano‐Stamps: A Versatile Approach for Imprinting Nanostructures

Abstract: In nanoimprint lithography (NIL), the imprinting stamp's fabrication is still a significant cost factor among the consumables. Bottom‐up lithography approaches based on a phase‐separation of polymer blends can provide a cost‐effective route for fabricating these stamps. Today's polymers used to prepare phase‐separated nanostructures (PSN), however, exhibit low glass transition temperatures. As a result, the PSN are prone to in‐plane stamp distortions in the presence of high imprinting pressure and temperature,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…[ 64 ] In addition, by using an inorganic‐organic hybrid UV‐curable resin, (i.e., OrmoStamp), the obtained porous polymer scaffold can serve as a nano‐stamp for imprinting nanostructures, confirming the versatility and up‐scalability of the polymer‐blend phase separation method. [ 65 ]…”
Section: Fabrication Methods For Making Light‐scattering Porous Polymersmentioning
confidence: 99%
“…[ 64 ] In addition, by using an inorganic‐organic hybrid UV‐curable resin, (i.e., OrmoStamp), the obtained porous polymer scaffold can serve as a nano‐stamp for imprinting nanostructures, confirming the versatility and up‐scalability of the polymer‐blend phase separation method. [ 65 ]…”
Section: Fabrication Methods For Making Light‐scattering Porous Polymersmentioning
confidence: 99%
“…Thermal nanoimprint lithography (NIL) is a low-cost, high-throughput technique that is used for transferring nanopatterns from a harder stamp to a sample material by direct mechanical deformation. , The stamp is typically a hard, resistant material that withstands the process conditions (pressure and temperature), such as silicon (oxide), nickel, or a hard curable polymer like OrmoStamp. , NIL has been widely used to transfer patterns to perovskite films as it was shown to be beneficial for the perovskite layer: During imprinting, the perovskite film recrystallizes, resulting in a film with improved crystal quality and higher stability against degradation. , Furthermore, it has been established that the NIL process results in fewer surface and structural defects in the film that serve as nonradiative recombination centers and are detrimental for lasing. ,, Next to the defect-assisted nonradiative losses, an essential parameter to consider for perovskite thin-film lasers is the waveguide propagation loss. This is strongly influenced by the surface roughness of the film, which can be greatly improved by imprinting with a smooth stamp. ,, Additional benefits of NIL are a precise control of the lasing wavelength due to a better control of the film thickness and the possibility to reuse a single stamp for fabricating multiple samples.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal nanoimprint lithography (NIL) is a low-cost, high-throughput technique that is used for transferring nanopatterns from a harder stamp to a sample material by direct mechanical deformation. 41 , 42 The stamp is typically a hard, resistant material that withstands the process conditions (pressure and temperature), such as silicon (oxide), nickel, or a hard curable polymer like OrmoStamp. 43 , 44 NIL has been widely used to transfer patterns to perovskite films as it was shown to be beneficial for the perovskite layer: During imprinting, the perovskite film recrystallizes, resulting in a film with improved crystal quality and higher stability against degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquid can be patterned with a UV imprinting technique, which is considered a cheaper and lower energy alternative than standard optical lithography or electron beam lithography as it relies on the replication of a master mold pattern. The method constitutes one of the most important patterning techniques and has found a widespread application in the fabrication of solar cells [ 22 ], optoelectronic and photonic devices [ 23 , 24 , 25 ]. It has been shown that titania nanoparticles (NPs) prepared in solution with ionic liquid can be directly imprinted by UV exposure using a flexible PDMS mold.…”
Section: Introductionmentioning
confidence: 99%